MOMENT-CURVATURE ANALYSIS OF GRADED CONCRETE BEAM WITH CONCRETE STRENGTH DISPARITY VARIATIONS - M. Mirza Abdillah Pratama; Moch. Febrian Andi; Christian Hadhinata (LPPM Universitas Negeri Jakarta, 2022)
The application of graded concrete on structural elements is predicted to increase the capacity of the structural performance, serviceability, and to reduce costs compared to conventional concrete structures. This study aims to analyze (1) the load-deflection relationship, (2) the moment-curvature, (3) the deflection ductility ratio, and (4) the crack pattern. This study used reinforced concrete (RC) beams specimens with the dimension of 13x19x150 cm which was categorized as reference specimens and graded concrete beams. For reference specimens, an RC beam possessing concrete strength of 30 MPa; 40 MPa; 50 MPa were prepared; For the graded concrete beams, two specimens made of 30-40 MPa; 30-50 MPa; 40-50 MPa were prepared. In terms of casting graded concrete beams, low-strength concrete is placed on the tensile fiber of the beam, while on the compressive fiber of the beam, high-strength concrete is placed. The specimens were tested using the four-point bending method. The results showed that the increase in the concrete strength in the compression fiber of the beam contributed to the increase in load capacity, stiffness, and serviceability in the post-crack phase. The increase of concrete strength in compression fibers by 20 MPa is considered effective and has a positive impact on the moment-curvature capacity and is considered efficient in construction costs. The deflection ductility of the beam is classified as partial ductile and is adequate for structural design in earthquake-prone areas. A flexural cracks pattern was found on each specimen.